Towards high-temperature applications of aluminium alloys enabled by additive manufacturing. (3rd April 2022) - Michi, Richard A.; Plotkowski, Alex; Shyam, Amit; Dehoff, Ryan R.; Babu, Sudarsanam Suresh
ABSTRACT: Research on powder-based additive manufacturing of aluminium alloys is rapidly increasing, and recent breakthroughs in printing of defect-free parts promise substantial movement beyond traditional Al–Si–Mg) systems. One potential technological advantage of aluminium additive manufacturing, however, has received little attention: the design of alloys for use at T > ~200°C, or ~1/2 of the absolute melting temperature of aluminium. Besides offering lightweighting and improved energy efficiency through replacement of ferrous, titanium, and nickel-based alloys at 200–450°C, development of such alloys will reduce economic roadblocks for widespread implementation of aluminium additive manufacturing. We herein review the existing additive manufacturing literature for three categories of potential high-temperature alloys, discuss strategies for optimizing microstructures for elevated-temperature performance, and highlight gaps in current research. Although extensive microstructural characterisation has been performed on these alloys, we conclude that evaluations of their high-temperature mechanical properties and corrosion responses are severely deficient.